The Islamic Law of War for Conflict Resolution: The Case of Boko Haram in Nigeria. - Owoade, Abdul Lateef (NIU Journal of Social Sciences; Vol 3 No 2 (2017): KIU Journal of Social Sciences, Vol. 3 No. 2, September 2017, 2017)
This paper attempts to look at the present situation of the boko haram crisis in Nigeria and the manner of resolution of the crisis under the Islamic Law. It starts by explaining the existence of the group, its origin, and then assesses the violent activities of the group which has culminated in panic and insecurity of life and properties around the nation. It appreciates the evidential threat of the group or sect to the unity of Nigeria while assessing the view of some experts on what they conceive to be the possible manner to resolve the crisis. It then goes further to analyze the manner of settling this crisis using the Islamic Law approach.